From what to where: neuropsychological evidence for implicit interactions between object- and space- based attention. - Humphreys, G; Jane Riddoch, M (2003)
Three experiments examined nonspatial extinction in G.K., a patient with bilateral parietal damage. Experiment 1 demonstrated nonspatial extinction (poor detection of a weak relative to a stronger perceptual group), even when the stronger group was less complex than the weaker group. Experiment 2 showed improved report of a letter falling at the location of the stronger group, but explicit judgments of the location of the letter were at chance. Experiment 3 replicated the object-cuing benefit, though G.K. could not discriminate whether a letter fell at the same location as the stronger perceptual group. The data indicate coupling between object- and space-based attention, so that spatial attention is drawn to the location occupied by the winner of object-based competition for selection. In this case, what cues where. This coupling operates implicitly, even when explicit location judgments are impaired.